PENGELOLAAN MADRASAH ALIYAH TERHADAP RENDAHNYA MINAT LULUSAN MELANJUTKAN KE PERGURUAN TINGGI - Aliyul Karror; Moh Rokib; Buna’i; Maimun (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2023)
This study aims to examine the factors that cause the low interest of graduates of Madrasah Aliyah Aomber Tambelengan in Somber Village to continue their education to higher education. Using a qualitative approach of the case study type, this study revealed that the low rate of study continuation is caused by internal factors, such as lack of awareness, low interest and motivation, as well as students' intellectual limitations, and external factors, such as family economic conditions, lack of parental support, and the influence of the social environment that is less supportive of higher education. Data was obtained through observation, interviews, and documentation, then analyzed through the stages of data condensation, data presentation, and conclusion drawn. The results of the study show that from year to year, the number of graduates who continue their education to higher education is very minimal, so management strategies from the madrasah are needed, including early mapping of students' interests, intensive counseling assistance, provision of scholarship information, and active involvement of families and communities in supporting students' academic aspirations.